2006
DOI: 10.1111/j.1439-0396.2006.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the tryptophan requirement of lactating sows. Part 2: Estimation of the tryptophan requirement by physiological criteria

Abstract: Mature sows were fed for a total of 72 lactations with diets which provided an adequate supply of energy and nutrients except for tryptophan (Trp). By supplementing a basal diet [native 1.2 g Trp/kg, equivalent to 0.8 g apparent ileal digestible (AID) Trp or 0.9 g true ileal digestible (TID) Trp] with L-Trp, five further diets (2-6) containing 1.5-4.2 g Trp/kg were formulated. The dietary Trp content had no effect on amino acid contents in milk on days 20 and 21 of lactation, but Trp in blood plasma on day 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These results suggest that Trp could promote the uptake of glucose through increasing insulin sensitivity. The meal tests performed in our experiment showed that the increase in the supply of dietary Trp increased the plasma Trp concentration in agreement with the previous results of Sève et al (1991) and Pampuch et al (2006). The blood concentrations of the other variables measured after the meal did not vary according to the dietary treatment except for the plasma insulin response, which was less in the Trp+ sows than in the Trp− sows at AF.…”
Section: Insulin Resistance and Dietary Supply Of Trpsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that Trp could promote the uptake of glucose through increasing insulin sensitivity. The meal tests performed in our experiment showed that the increase in the supply of dietary Trp increased the plasma Trp concentration in agreement with the previous results of Sève et al (1991) and Pampuch et al (2006). The blood concentrations of the other variables measured after the meal did not vary according to the dietary treatment except for the plasma insulin response, which was less in the Trp+ sows than in the Trp− sows at AF.…”
Section: Insulin Resistance and Dietary Supply Of Trpsupporting
confidence: 92%
“…A deficient as well as an excessive dietary supply of Trp impairs the appetite of lactating sows (Lewis and Speer, 1974;Paulicks et al, 2006). The actual recommendation for the Trp:Lys ratio in the lactation diet is 18% (Dourmad et al, 1991;NRC, 1998) but was recently estimated at 24% on the basis of feed intake and uremia (Pampuch et al, 2006;Paulicks et al, 2006). However, these authors studied multiparous sows only, and the effect of such a dietary Trp concentration on the performance of lactating primiparous sows remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…1 where plasma Thr increased linearly with increasing Thr intake in LG. Plasma AA have been shown to correlate poorly with other estimates of requirement or to respond linearly to all treatments (Mitchell et al, 1968;Sohail et al, 1978;Pampuch et al, 2006) and thus are less reliable dependent variables when estimating AA requirements. The quantitative response of plasma AA to changes in dietary AA reflects the complex interaction of the dynamic equilibrium of the plasma AA pool with the tissue AA pool, protein degradation, and labile nonprotein AA sources (Young and Scrimshaw, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more research should be conducted on the effects of tryptophan supplementation on sow behaviour and serotonin production to understand how tryptophan affects piglet survival. Furthermore, serotonin production may not increase linearly with increasing tryptophan levels [ 21 ]; thus, the similar survival rates seen in both High and Low tryptophan may be attributed to High tryptophan having a plateauing effect on serotonin production.…”
Section: Discussionmentioning
confidence: 99%
“…Most maternal tryptophan supplementation studies in sows have focussed on sow performance indices such as lactational weight loss and milk yield. Although benefits for piglet survival and weights have been shown [ 10 , 11 , 21 , 22 , 23 ], the impact of tryptophan on piglet viability has yet to be established. Furthermore, increasing levels of calcium and melatonin through tryptophan supplementation has only been studied in cattle, sheep and rats, respectively, and have not been established in sows [ 17 , 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%